The Synergistic Effect of Nicotine and Staphylococcus aureus on Peri-Implant Infections - Hu, Yao; Zhou, Wen; Zhu, Chengguang; Zhou, Yujie; Guo, Qiang; Huang, Xiaoyu; Yang, Bina; Ren, Biao; Cheng, Lei (Frontiers in Bioengineering and Biotechnology, 2021)
Smoking is considered a key risk factor for implant survival; however, how it interacts with the pathogens in peri-implant infections is not clear. Here, we identified that nicotine, the key component of cigarette smoking, can interact with Staphylococcus aureus and synergistically induce peri-implant infections in a rat osteolysis model. The nicotine–S. aureus combination group increased the gross bone pathology, osteolysis, periosteal reactions, and bone resorption compared to the nicotine or S. aureus single treated group (p < 0.05). Nicotine did not promote the proliferation of S. aureus both in vitro and in vivo, but it can significantly upregulate the expression of staphylococcal protein A (SpA), a key virulence factor of S. aureus. The nicotine–S. aureus combination also synergistically activated the expression of RANKL (receptor activator of nuclear factor-kappa B ligand, p < 0.05) to promote the development of peri-implant infections. The synergistic effects between nicotine and S. aureus infection can be a new target to reduce the peri-implant infections.